First-trimester determination of fetal gender by ultrasound: measurement of the ano-genital distance. (August 2016) - Arfi, A.; Cohen, J.; Canlorbe, G.; Bendifallah, S.; Thomassin-Naggara, I.; Darai, E.; Benachi, A.; Arfi, J.S.
Abstract: Introduction: Early ultrasound fetal sex determination is of obvious interest, particularly in the context of X-linked diseases. In the human, the anogenital distance, i.e., the distance between the caudal end and the base of the genital tubercule is sexually dimorphic. This difference is apparent from 11 weeks of gestation. The aim of this prospective study was to evaluate the accuracy of anogenital distance measurement during the first trimester ultrasound in the early determination of fetal gender. Materials and methods: Fetal gender was assessed by ultrasound in 310 singleton pregnancies at 11–14 weeks of gestation. The optimal cut-off was determined by the minimal p -value technic and validated using bootstrap simulation. Results: 310 women were included. A cut-off of 4.8 mm was determined to predict male (≥4.8 mm) or female (<4.8 mm) fetuses. Sex was correctly determined for 87% of the males and 89% of the females. The inter-observer variability was excellent. Conclusion: This study presents a new sonographic sign for early fetal sex determination that has not been previously explored. It appears to be an accurate tool but it requires further validation in larger series.